ChemInform Abstract: Synthesis of [(SnSe)1.15]m(TaSe2)n Ferecrystals: Structurally Tunable Metallic Compounds. Issue 11 (8th March 2013) - Atkins, Ryan; Wilson, Jason; Zschack, Paul; Grosse, Corinna; Neumann, Wolfgang; Johnson, David C.
Abstract The title ferecrystals (fere: Latin, almost) with 1 ≤ n, m ≤ 6 and n and m varied independently are prepared by physical vapor deposition of the elements followed by annealing at 400 °C for 30 min.